Evolution characteristics and driving factors of negative decoupled rural residential land and resident population in the Yellow River Basin. (October 2021) - Shi, Linna; Wang, Yongsheng
Abstract: The Yellow River Basin (YRB) is an important ecological barrier in China, which is the fifth largest river all over the world. Protecting YRB is crucial to China's rejuvenation and sustainable development of future generations. Coordinated development of human-land system is conducive to promoting ecological protection and high-quality development of YRB. Tapio decoupling model was used to study the relationship between rural residential land area and resident population. Our results showed that the rural resident population decreased by 2.57% annually, while rural residential land areas expanded at a rate of 0.57% from 2010 to 2016. In addition, the upper reaches had higher growth rate of residential land area than that in the middle and lower reaches. The strong negative decoupling relationship between rural residential land area and rural resident population was widely found in YRB. Kaya identity decomposition results indicated that rural residential land intensive utilization and urbanization of resident population was positively related to the expansion of rural residential land area, while the urban and rural population structure was responsible for rural residential land area shrinkage in YRB. Unfavorable rural development situation had extended from 2010 to 2016. These results suggested that the rural human-land relationship was uncoordinated in terms of the loss of rural resident population and expansion of rural residential land area in YRB. It is urgent to establish sustainable rural development strategies for improving the human-land relationship, narrowing the rural-urban disparity, innovating rural residential land area policies, and revitalizing the rural area. Highlights: Decoupled relationship between rural residential land and resident population was explored in Yellow River Basin. Population, intensive land rural residential utilization, and urbanization promoted the rural residential land expansion. The urban and rural population structure was responsible for rural residential land shrinkage. Policies were suggested to optimize the relationships between residential land and resident population in rural areas.